Pest Diversity Classification for Insectiside Application Frequency Treatment on Melon Plants - Febriyanti, Salsabila Salma; Risnawati, Risnawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Melon (Cucumis melo L.) is one of the high-value horticultural commodities with continuously increasing market demand. However, its productivity is often hindered by major pest attacks such as aphids (Aphis gossypii), fruit flies (Bactrocera spp.), and armyworms (Spodoptera sp.). This study aims to analyze the effect of the frequency of insecticide application containing the active ingredient deltamethrin on pest attack intensity and melon plant growth parameters, pest classification. The study was conducted at UG Techno Park, Cianjur, from February to June 2025 using a nested completely randomized block design (CRBD) with the Inthanon and Madesta varieties. The treatments included insecticide application every 7 days, every 14 days, and no application (control). The results showed that insecticide application every 7 days reduced pest attack intensity to 12.25%. The Madesta variety performed best with a pest attack intensity of 11.04% and fresh harvest weight reaching 1.743.75 grams per plot. The combination of insecticide application strategies and CNN-based classification has proven effective in improving pest identification accuracy and supporting precise and sustainable pest control.